Kesehatan Reproduksi Remaja Terkait Status Gizi, Aktifitas Fisik, Stres Dengan Siklus Menstruasi - Damayanti, Dewi Suri; Munawaroh (Universitas Mohammad Husni Thamrin, 2024)
Abstract The menstrual cycle is an important indicator of women's reproductive health (Omidvar et al., 2018). According to the research conducted at SMA Negeri 6 Tangerang, a higher proportion of irregular menstrual cycles was found, amounting to 59.4%. The impacts of irregular menstruation include infertility, endometriosis, and psychological disorders (Ilmi & Selasmi, 2019). The current target of the researchers is adolescents because adolescent reproductive health, especially regarding the menstrual cycle, is necessary for reproductive health readiness in adulthood. The research method used is descriptive quantitative with a cross-sectional approach. The research respondents are high school students. The purpose of this study is to determine adolescent reproductive health related to nutritional status, physical activity, and anxiety with the menstrual cycle in high school. The study results showed that the majority experienced irregular menstrual cycles, with 74 respondents (78.7%). The three variables studied, namely nutritional status, physical activity, and stress among high school students, showed no difference in proportion. This is because, during adolescence, the body adapts to hormonal changes during puberty, so the menstrual cycle still varies. This is considered normal. As age increases, the menstrual cycle will stabilize and become regular, especially after age 20 (Musmiah, 2018). During data collection, it was found that respondents still did not understand how to calculate the menstrual cycle, so efforts are needed to increase knowledge and understanding of their menstrual cycles.